The Customer Success Professional's Handbook - Vaidyanathan, Ashvin; Rabago, Ruben (Ascent Audio, 2020)
The Customer Success Manager has become a critical asset to organizations across the business landscape. As the subscription model has spread from the cloud and SaaS to more sectors of the economy, that pivotal role will only grow in importance. That's because if you want to compete and thrive in this new environment, you need to put the customer at the center of your strategy. You need to recognize you're no longer selling just a product. You're selling an outcome. Customer Success Managers (CSM) are committed to capturing and delivering those outcomes by listening to their customers, understanding their needs, and adapting products and services to drive success. Although several existing resources address the customer success imperative, there is no authoritative instruction manual for the CSM profession-until now. The Customer Success Professional's Handbook is the definitive reference book for CSMs and similar roles in the field. This practical, first-of-its-kind manual fills a significant gap in professional customer success literature, providing the knowledge every CSM needs to succeed-from the practitioner level all the way to senior leadership. The authors-acknowledged experts in building, training, and managing Customer Success teams-offer real-world guidance and practical advice for aspiring and experienced CSMs alike.
Online resource; Title from title page (viewed March 24, 2020)
Keywords: Business; Affaires; Audiobooks